As quatro estações: o vai e vem das estações - Faquini , Josieli Loise de Queiros Silva; Donini, Luciana Neves; Bernhardt, Cristiane Otilia Colossi (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2023)
>>> ver pdf